Test of Stoping Power of Peel-Off Masker Gel Combination of Kelor Leaf Extract (Moringa Oleifera L) and Kunyit Extract (Curcuma Domestica Val) Against The Bacteria Staphylococcus Aureus) - Rahmah Rahmah; Suryadi Imran; Shonia Khoirunnisa (West Science Interdisciplinary Studies, 2025)
The peel off gel mask of Moringa leaves and turmeric is a skin care cosmetic preparation in the form of a gel and after being applied to the skin within a certain time it will dry out which is used as an anti-acne. This study aims to determine the inhibitory ability of the peel off gel mask combination of Moringa leaf extract and turmeric extract against Staphylococcus aureus bacteria for each formula and to determine the best formulation with maximum inhibitory value. The type of research used in this research is Quasy Experimental research. The results showed that Moringa leaf extract and turmeric were able to inhibit the growth of Staphylococcus aureus bacteria with an average diameter of the inhibition zone for each formula, namely F1 (7%: 3%) which was 12.44 mm, F2 (6%: 4%) was 12, 14 mm, F3 (5% : 5%) is 12.00 mm, F4 (4% : 6%) is 11.84 mm, and F5 (3% : 7%) is 11.66 mm, then for alcohol ( 96%) = 10 mm, and for positive control (clindamycin) = 34 mm, and negative control (aquadest) = 0 mm. All the results of the inhibition test were included in the strong category. The best formulation is shown by F1 which is 12.44 mm.